The recipient becoming a participant and the participant becoming a recipient: A strange encounter in 1 Kings 17 with a not so strange outcome - J.S. van der Walt (Acta Theologica)
A narrative in 1 Kings 17:1-16 tells of a strange encounter between two people of different backgrounds, one is a prophet of YHWH and the other is a dying widow. Dialogue brings them closer to each other in a mysterious way, causing them to change roles. In doing so, they come to realise that the trust they have for each other has an origin far deeper than they could imagine.